50.7k views
5 votes
Subtract (5x + 3) from (9x – 7).

User Guilhebl
by
6.3k points

2 Answers

4 votes

Answer:


\large\boxed{4x-10}

Explanation:


(9x-7)-(5x+3)\\\\=9x-7-5x-3\qquad\text{combine like terms}\\\\=(9x-5x)+(-7-3)\\\\=4x-10

User Argelia
by
6.2k points
4 votes

Answer:

4x - 11

Explanation:

Set the expression.

9x - 7

- (5x + 3)

-------------

First, distribute -1 to all terms within the parenthesis:

-(5x + 3) = -5x - 3

Simplify. Combine like terms.

(9x - 7) + (-5x - 3) = 9x - 5x + (-7) - 3

(9x - 5x) + (-7 - 3)

4x - 11

4x - 11 is your answer.

User Ron Klein
by
5.3k points